2012
DOI: 10.1016/j.nbd.2011.07.014
|View full text |Cite
|
Sign up to set email alerts
|

A canine BCAN microdeletion associated with episodic falling syndrome

Abstract: Episodic falling syndrome (EFS) is a canine paroxysmal hypertonicity disorder found in Cavalier King Charles spaniels. Episodes are triggered by exercise, stress or excitement and characterized by progressive hypertonicity throughout the thoracic and pelvic limbs, resulting in a characteristic 'deer-stalking' position and/or collapse. We used a genome-wide association strategy to map the EFS locus to a 3.48 Mb critical interval on canine chromosome 7. By prioritizing candidate genes on the basis of biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
52
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 29 publications
3
52
0
Order By: Relevance
“…18 On postmortem examination, a variety of changes have been described in skeletal muscle, such as enlargement and proliferation of the sarcoplasmic reticulum, but these are likely to be secondary to excessive muscle contractions. 14,15,19 Recently, this dramatic condition has been linked to a deletion in the gene BCAN 18,19 that encodes a protein called brevican. This protein is a component of the extracellular matrix proteoglycan complex and is found at high levels in the central nervous system as part of the perineuronal network.…”
Section: Inherited Diseases Episodic Falling In Cavalier King Charlesmentioning
confidence: 99%
See 1 more Smart Citation
“…18 On postmortem examination, a variety of changes have been described in skeletal muscle, such as enlargement and proliferation of the sarcoplasmic reticulum, but these are likely to be secondary to excessive muscle contractions. 14,15,19 Recently, this dramatic condition has been linked to a deletion in the gene BCAN 18,19 that encodes a protein called brevican. This protein is a component of the extracellular matrix proteoglycan complex and is found at high levels in the central nervous system as part of the perineuronal network.…”
Section: Inherited Diseases Episodic Falling In Cavalier King Charlesmentioning
confidence: 99%
“…It is proposed that disruption of these extracellular complexes results in alterations in nerve conduction and in synaptic stability. 19 As is typical for all genetic disease, there is phenotypic variability and both research groups that described the mutation identified dogs homozygous for the mutation, but with no reported clinical signs. They theorized that these dogs may simply not have exerted themselves to the point of producing signs, but it is important to note that mouse BCAN knockouts are clinically normal.…”
Section: Inherited Diseases Episodic Falling In Cavalier King Charlesmentioning
confidence: 99%
“…Type 2 fiber atrophy in this case may be the result of disuse or altered patterns of neural excitability to the muscle fibers. The affected puppy, unaffected littermates, the dam and the sire all tested negative for the BCAN microdeletion that results in episodic falling syndrome in Cavalier King Charles spaniels (CKCS) (Forman et al 2012;Gill et al 2012). The parents and littermates did not show any signs of hypertonicity.…”
mentioning
confidence: 99%
“…An abnormality in CNS neurotransmission was suspected in CKCS and a microdeletion in the brevican gene (BCAN) was identified (Forman et al 2012;Gill et al 2012). Brevican has an essential role in the formation of perineuronal nets governing synapse stability and nerve conduction velocity (Gill et al 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation